2008
DOI: 10.1111/j.1540-6237.2008.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oklahoma's Pre‐K Program on Hispanic Children*

Abstract: Objective. The objective of this work is to determine how much Hispanics benefit from a high‐quality pre‐K program and which Hispanic students benefit the most. Methods. Hispanic students in Tulsa, Oklahoma were tested (in English, Spanish) in August 2006. A regression discontinuity design addressed potential selection bias by comparing pre‐K alumni (treatment group) with pre‐K entrants (control group), controlling for age and other demographic variables. Results. Hispanic students experienced substantial im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 25 publications
5
90
0
1
Order By: Relevance
“…For example, the first-year findings from the Head Start Impact Study showed broader benefits of Head Start participation for the cognitive and socioemotional school readiness skills of children from primarily Englishspeaking versus Spanish-speaking households (ACF, 2005). However, Gormley (2008) found that center-based prekindergarten benefits for academic skills were larger for children from non-English-speaking households than for children from English-speaking households.…”
Section: Heterogeneity Among Children Of Immigrantsmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, the first-year findings from the Head Start Impact Study showed broader benefits of Head Start participation for the cognitive and socioemotional school readiness skills of children from primarily Englishspeaking versus Spanish-speaking households (ACF, 2005). However, Gormley (2008) found that center-based prekindergarten benefits for academic skills were larger for children from non-English-speaking households than for children from English-speaking households.…”
Section: Heterogeneity Among Children Of Immigrantsmentioning
confidence: 92%
“…Research has uncovered cognitive and language benefits of center-based EEC for children of immigrants that are equal to or larger than those for children of native parents (ACF, 2005;Crosnoe, 2007;Gormley, 2008;Magnuson et al, 2006). For example, using a rigorous regression discontinuity design, Gormley (2008) found more consistent and sometimes larger spelling, reading, and math skills benefits of prekindergarten attendance for children of Mexican immigrant parents compared to Hispanic students whose parents were born in the United States. Little research has focused on behavioral outcomes.…”
Section: Conceptual and Empirical Foundations: Eec And School Readinementioning
confidence: 95%
See 1 more Smart Citation
“…Heckman (2011) noted that because the early years are the most critical, the provision of high-quality early care and education (ECE) can yield the highest rate of return to human capital investment, and high quality ECE programs are essential if we are to close the well-documented achievement gap (Gormley, Gayer, Phillips, & Dawson, 2004;Henry, Gordon, Henderson, & Ponder, 2003;King, 2006;Reynolds et al, 2001;Schulman, 2005;Schulman & Barnett, 2005;Schweinhart et al, 2005). Findings from the National Center for Early Development and Learning (NCEDL) indicated that when young children are exposed to high-quality instructional interactions with teachers, they develop 47 academic, language, and social competencies (LoCasale-Crouch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although still expensive and time consuming, the technology is continuing to improve. Achieving a detailed understanding of exactly what is occurring in classrooms, rather than continuing to treat this important proximal influence like a "black box," appears to be worth the time and expense, especially given society's real and potential investment in preschool interventions (Gormley, Gayer, Phillips, & Dawson, 2004;Sawhill, 1999) and new universal prekindergarten initiatives (e.g., Florida).…”
Section: Research Implicationsmentioning
confidence: 99%